Twinning elements of 2-nd order derived from crystal lattice parameters in central-symmetrical ferroelastics - Savytskii, D.I. (Functional Materials, 2007)
The algorithm for determination of possible second order twinning laws—mirror planes and twofold axes is presented. The method is applicable for center-symmetrical ferroelastics and/or twins with non-zero obliquity. The proposed algorithm allows to determine twinning elements using only known crystal lattice parameters without additional analysis of correlation of para- and ferroelastic phase point groups or using other theoretical methods of twin structure forecast.